An Explanation of Energy Return on Investment From an Entropy Perspective - Hu, Yan; Chen, Yingchao; Tang, Songlin; Feng, Lianyong; Huang, Chen (Frontiers in Energy Research, 2021)
Low-carbon energy transformation is a major trend in world energy development, and measures to mitigate carbon emissions can vary substantially in terms of the energy they require. A common method of evaluating energy use in energy resource exploitation is energy return on investment (EROI). One of the criticisms of EROI concerns uncertainty regarding the input and output factors for the calculation. To make the issue clear, we interpret EROI in terms of entropy, which is the most basic concept in physics. We consider an energy resource exploitation system to be a kind of dissipative structure and construct a basic entropy analysis framework for an energy resource exploitation system. We then derive the relationship between EROI and entropy change. The theory of EROI is consistent with the basic requirement for a dissipative structure, which is that the total entropy change must be negative. EROI is a method of using entropy theory to evaluate energy resource exploitation. It is inappropriate and unnecessary to quantify all factors as energy units as the input and output factors are multidimensional while energy is a one-dimensional standard. Future development of the EROI method should be guided by entropy theory. A series of EROI related indicators will increase its application and policy significance.